Achieving democracy through interest representation : interest groups in Central and Eastern Europe /: interest groups in Central and Eastern Europe. (2021) - Rozbicka, Patrycja; Kamiński, Paweł, 1958-; Novak, Meta; Jankauskaite, Vaida
No abstract available